2021
DOI: 10.21203/rs.3.rs-576430/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deciphering Biochemical Responses, Metabolome Analysis and Key Genes Controlling Sorghum [Sorghum Bicolor (L.) Moench] Ion Transport in Responses to Salt Stress

Abstract: Background: Crops usually encounter several abiotic stresses, and salt stress is one of the major constraints affecting plant growth and agricultural productivity globally. Sorghum is not only a valuable source of food but also a potential model for studying and better understanding the salt stress mechanics in the cereals and obtain a better knowledge of their cellular mechanism. Herein, we examined the effects of salt stress on physio-biochemical and molecular responses of sorghum genotypes to determine thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Hassan et al [37] observed that ash content represents an index of high minerals that improved the overall performance of seed quality. Dietary fiber promotes the food absorption and bowel movement through the small intestine [39]. Bottle gourd is a rich source of dietary fibers that expand food inside the colon wall, easing the passage of waste and making it an effective anti-constipation agent.…”
Section: Discussionmentioning
confidence: 99%
“…Hassan et al [37] observed that ash content represents an index of high minerals that improved the overall performance of seed quality. Dietary fiber promotes the food absorption and bowel movement through the small intestine [39]. Bottle gourd is a rich source of dietary fibers that expand food inside the colon wall, easing the passage of waste and making it an effective anti-constipation agent.…”
Section: Discussionmentioning
confidence: 99%
“…They are used in irrigation, water purification, carbon nanotubes nano-enabled membrane filters, and ceramic and magnetic particles for water management. Irrigation water can be treated with some available devices, e.g., nano-8630 for improving crop performance [ 6 , 8 , 9 , 14 , 16 , 50 , 51 , 52 , 53 , 54 ]. Different methods, such as bench terracing, counterbidding, and micro-irrigation systems as ex-situ methods and tillage (Zero, Minimum, and Conservation), cultural practices (furrow and ridge sowing), and some chemicals, such as anti-transpirants and super absorbent polymers, can be used as in-situ for preserving and shrinking water application in the field.…”
Section: Nano-irrigation For Solving the Irrigation Problem In Agricu...mentioning
confidence: 99%